ANALISIS STRATEGI PEMASARAN DENGAN METODE SWOT DAN QSPM INTEGRASI ANALYTIC HIERARCHY PROCESS DI COFFEE SHOP MOJA KITCHEN - Herlinda Novitasari; Didi Samanhudi (Fakultas Ekonomi Universitas 45 Surabaya, 2021)
This study aims to explain and formulate marketing alternatives that can be seen from the internal and external conditions in the Mojo Kitchen Coffee Shop Business at Jln Bhaskara No. 5 City of Surabaya. This research uses SWOT analysis (Strength, Weakness, Opportunities, Threats) and QSPM (Quantitative Strategic Planning Matrix) using AHP Integration to Explain and Formulate Marketing Strategies. 5 City of Surabaya. Internal environmental analysis is used to get the strengths and weaknesses of the Mojo Kitchen Coffee Shop, and external environmental analysis is used to get opportunities and threats to the Mojo Kitchen Coffee Shop. From the results of the SWOT analysis (Strength, Weakness, Opportunities, Threats), there are two SO (Strength Opportunity) Strategies, Two WO Strategies (Weakness Opportunity), Two ST (Strength Threat) Strategies, and Two WT (Weaknes Threat) Strategies. From the results of the four strategies, one strategy that is more superior or prioritized is selected by performing a QSPM (Quantitative Strategic Planning Matrix) analysis. From the results of the QSPM analysis, it is found that one more strategy is prioritized based on the largest total value of attraction (TAS). The strategy that gets the largest total attractiveness value (TAS) is Staregi 3 providing more products than various other coffee shops with a total attractiveness value of 5,852.